Um olhar para estudantes com deficiência em contextos empobrecidos - Silva, Carla Briseida Choque Villarroel (2024)
This work aims to understand whether and how the condition of poverty shapes the schooling process of students with disabilities. To fulfill this investigative purpose, we looked for a school in a peripheral neighborhood in the municipality of Vila Velha, Espírito Santo, Brazil surrounded by two ocupations. The data collected weaves reflections in dialogue with the literature that deals with the themes of poverty and disability. In methodological terms, this work is outlined as qualitative research, using as a reference the assumptions of Figurational Sociology, developed by Norbert Elias (1994; 2014). The data presented presents the characterization of the school through socioeconomic data from the School Management System (SGE, 2024) and semistructured interviews. The analysis of this set of data allowed us to observe that the school shows that (79.23%) of the families live with a monthly income of less than 1820.00 reais and that the majority of households (57.62%) are the responsibility of mothers and that in the case of students with disabilities, mothers dedicate themselves exclusively to the student's care, which is why many depend on social benefits. Data referring to the territory shows that students who live in impoverished contexts face weaknesses and are affected by hunger, lack of infrastructure, violence in the territory and access to health, being one of the main difficulties presented by families of students with disabilities. Added to these variants are the stigmas experienced by the condition of poverty and disability, which have historically accompanied the poor and disabled throughout the social process and outline the daily lives of students in impoverished contexts and their schooling process shaped in the fabric of moving relationships that narrate their schooling. The data systematized in this study encourage us to consider that the principles of universality and equity of rights presuppose the creation and implementation of policies that consider poverty in school spaces, as the school alone cannot face such a challenge, on the contrary, the school comes being crossed by this context.